Expression of carboxyl terminus of Hsp70-interacting protein (CHIP) indicates poor prognosis in human gallbladder carcinoma - LIANG, ZHE LONG (D.A. Spandidos, 2013)
Gallbladder carcinoma (GBC) is a lethal neoplasm, and new prognostic markers are required. Deregulation of E3 ligases contributes to cancer development and is associated with poor prognosis. Carboxyl terminus of heat shock protein 70-interacting protein (CHIP) is a U-box-type E3 ubiquitin ligase, the role of which has not been evaluated in GBC. Therefore, the present study investigated CHIP expression in GBC and its prognostic significance. In the present study, CHIP expression was measured in 78 tumor specimens of GBC by immunohistochemistry and the correlation between CHIP expression and clinicopathological factors was analyzed. Of the tumor specimens, 26.9% showed high staining intensity [the CHIP high expression group (HEG)]. The CHIP-HEG was not associated with other common clinicopathological parameters, including T stage, and lymph node and distant metastases. CHIP-HEG patients had a significantly worse prognosis than patients with low CHIP expression with median cancer-specific survival times of 8.0 months (range, 1–34 months) and 13.0 months (range, 1–110 months), respectively (P=0.023). Multivariate analyses showed that CHIP expression was close to being an independent risk factor for predicting patient survival. CHIP expression may be associated with a poor prognosis in GBC. Since CHIP is not associated with other clinicopathological prognostic factors, it may serve as an ideal molecular marker for predicting patient outcomes.